ANALISIS ASPEK TEKNIS, SOSIAL, LINGKUNGAN DAN EKONOMI DALAM PEMILIHAN LOKASI EMBUNG KECIL DI PULAU SABU, NUSA TENGGARA TIMUR (NTT) - I Gede Oka Wiradnyana (Universitas Pendidikan Nasional, 2018)
East Nusa Tenggara (NTT) province, especially in Sabu Island, is one of the mostfrequently drought areas, especially in the dry season, when the rainy season is relatively short eachyear (± 4 months per year). Thus, the government, both from the local government and centralgovernment keep on to program the implementation of small reservoirs development work in all islandsin NTT, including in Sabu Island. The government and the community hope that the development ofthe small reservoir is targeted, where the location is possible and indispensable, with efficient(economic) usage, technical qualifications, and no problem with land status.Data collection is done by observation and interview with some elements of prospective usersof small reservoir in nine locations. The data are classified into several aspects, namely technical, social,environmental, economic and land status aspects of each location. The data is given an assessment ofall aspects, then summarized all the results of the assessment.The results of data processing showed that the factors that influence the site selection of smallreservoir locations on Sabu Island are technical, social, environmental, economic and land status. 5 sitesof the most ideal small reservoirs location built on Sabu Island, so it is not redundant and can be utilizedwell by the community of water users of small reservoirs is Embung Kili with points (values) 84, HangaLui Hara (82), Hanga Kepaka (81), Lobala ( 81), Ketu Ke'bao (70).